Skeletal Muscle-Specific CPT1 Deficiency Elevates Lipotoxic Intermediates but Preserves Insulin Sensitivity - Wanchun Shi; Siping Hu; Wenhua Wang; Xiaohui Zhou; Wei Qiu (Journal of Diabetes Research)
Objective. By specific knockout of carnitine palmitoyl transferase 1b (CPT1b) in skeletal muscles, we explored the effect of CPT1b deficiency on lipids and insulin sensitivity. Methods. Mice with specific knockout of CPT1b in skeletal muscles (CPT1b M−/−) were used for the experiment group, with littermate C57BL/6 as controls (CPT1b). General and metabolic profiles were measured and compared between groups. mRNA expression and CPT1 activity were measured in skeletal muscle tissues and compared between groups. Mitochondrial fatty acid oxidation (FAO), triglycerides (TAGs), diglycerides (DAGs), and ceramides were examined in skeletal muscles in two groups. Phosphorylated AKT (pAkt) and glucose transporter 4 (Glut4) were determined with real-time polymerase chain reaction (RT-PCR). Insulin tolerance test, glucose tolerance test, and pyruvate oxidation were performed in both groups. Results. CPT1b M−/− model was successfully established, with impaired muscle CPT1 activity. Compared with CPT1b mice, CPT1b M−/− mice had similar food intake but lower body weight or fat mass and higher lipids but similar glucose or insulin levels. Their mitochondrial FAO of skeletal muscles was impaired. There were lipids accumulations (TAGs, DAGs, and ceramides) in skeletal muscle. However, pAkt and Glut4, insulin sensitivity, glucose tolerance, and pyruvate oxidation were preserved. Conclusion. Skeletal muscle-specific CPT1 deficiency elevates lipotoxic intermediates but preserves insulin sensitivity.